2018 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2018
DOI: 10.1109/pesgm.2018.8586415
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Nonlinear Control for Power Systems using Normal Forms and Detailed Models

Abstract: This paper proposes a decentralized method for nonlinear control of oscillatory dynamics in power systems. The method is applicable for ensuring both transient stability as well as small-signal stability. The method uses an optimal control law which has been derived in the general framework of nonlinear control using normal forms. The model used to derive the control law is the detailed subtransient model of synchronous machines as recommended by IEEE. Minimal approximations have been made in either the deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…This is the widely used strategy in the current literature. The high-performance computing techniquebased DSE for large-scale systems is in its infancy and merits further research; • Enhanced hierarchical decentralized control [18]- [20]: the availability of local and wide-area dynamic states obtained from DSE enables the design of effective local and wide-area controls; for instance, the estimated rotor speed and other states can be used as input signals to control excitation systems of synchronous machines [19], [20] or of FACTS devices [18] so as to damp out oscillations. The implementation can be in either fully decentralized or hierarchically decentralized manner; • Improved dependability and reliability of protection systems [6], [21]- [23]: by testing the consistency between the PMU measurements and the dynamical model of the protection zone for which the parameters are identifie by DSE, both internal and external faults can be effectively detected without any a priori protection relay settings, yielding more reliable protection systems compared with the traditional coordinated settings-based schemes; the estimated online dynamic states can be utilized to initiate effective generator out-of-step protections [9], [23] and transient stability monitoring based on the extended equal-area criterion or the energy function approach [23]; furthermore, fast state estimation is a prerequisite for the implementation of system integrity protection schemes that can prevent blackouts; • Enhanced reliability of the system models utilized for dynamic security assessment (DSA) [24]: DSA requires the availability of accurate models of the generators and their associated controllers, of the composite loads and of the special protection schemes, to name a few.…”
Section: Motivations For Dynamic State Estimationmentioning
confidence: 99%
“…This is the widely used strategy in the current literature. The high-performance computing techniquebased DSE for large-scale systems is in its infancy and merits further research; • Enhanced hierarchical decentralized control [18]- [20]: the availability of local and wide-area dynamic states obtained from DSE enables the design of effective local and wide-area controls; for instance, the estimated rotor speed and other states can be used as input signals to control excitation systems of synchronous machines [19], [20] or of FACTS devices [18] so as to damp out oscillations. The implementation can be in either fully decentralized or hierarchically decentralized manner; • Improved dependability and reliability of protection systems [6], [21]- [23]: by testing the consistency between the PMU measurements and the dynamical model of the protection zone for which the parameters are identifie by DSE, both internal and external faults can be effectively detected without any a priori protection relay settings, yielding more reliable protection systems compared with the traditional coordinated settings-based schemes; the estimated online dynamic states can be utilized to initiate effective generator out-of-step protections [9], [23] and transient stability monitoring based on the extended equal-area criterion or the energy function approach [23]; furthermore, fast state estimation is a prerequisite for the implementation of system integrity protection schemes that can prevent blackouts; • Enhanced reliability of the system models utilized for dynamic security assessment (DSA) [24]: DSA requires the availability of accurate models of the generators and their associated controllers, of the composite loads and of the special protection schemes, to name a few.…”
Section: Motivations For Dynamic State Estimationmentioning
confidence: 99%
“…In the last two decades, NF results had revealed that the interactions among modes have strong effects in the control designs and transient stability of power system [12], [21]. In testimony of this, better nonlinear control designs using NF are being developed [17], [22]- [24]. The authors in [25] showed that power system stability sub-modes interact with each other, especially when the power system presents strong nonlinear characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the power system literature modification in the excitation controllers is suggested to improve the overall system stability, using mainly normal forms [17, 18] or Lyapunov methods [19]. To the best of our knowledge, modification in the excitation controllers is not reported, in the context of yielding robust phase characteristics of the GEP TF.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this end, for the first time, we are investigating a novel modification in the excitation controller rendering robust phase characteristics. Excitation controllers reported in [17–19] have following shortcomings, (i) voltage regulation is not incorporated and requires a large number of plant signals, (ii) wrong formulation leading to higher damping of rotor modes and many plant signals are required, and (iii) no guidelines to tune the controller gains. Most interestingly, we observed that a term ‘Vt/Vq’ is the common among three excitation controllers.…”
Section: Introductionmentioning
confidence: 99%